“HAPPY BREASTFEEDING” VIDEO FOR INCREASING BREASTFEEDING MOTHER KNOWLEDGE - Kharisma Virgian; Desy Setiawati (Institute of Computer Science (IOCS), 2022)
Breastfeeding is a natural process in a mother's life. The Mother's knowledge of the breastfeeding factor supports success in providing breast milk. One of the media for increasing maternal knowledge is breastfeeding education videos. This study aims to find out the effect of happy breastfeeding videos on improving the knowledge of breastfeeding mothers. The respondent of this researach are 33 mother who had 0-12 month babies from independent midwifey practice in Palembang city. This study used a quasi-experiment research design using one-group pre-test and post-test design approaches. The group of breastfeeding mothers was measured twice, before and after using this video. Using the Mc Nemmar test, this study found significant differences in maternal knowledge before and after using happy breastfeeding videos ( ρ=0.000). Using more exciting and innovative educational media to improve maternal knowledge further improves maternal knowledge and supports breastfeeding success.